A 1-V 4-mW Differential-Folded Mixer with Common-Gate Transconductor Using Multiple Feedback Achieving 18.4-dB Conversion Gain, +12.5-dBm IIP3, and 8.5-dB NF - Vitee, Nandini; Ramiah, Harikrishnan; Mak, Puk In; Yin, Jun; Martins, Rui Paulo (Institute of Electrical and Electronics Engineers, 2020)
This article reports a novel differential-folded mixer with multiple-feedback techniques for performance enhancement. Specifically, we introduce the capacitor cross-coupled (CCC) common-gate (CG) transconductance stage to improve the noise figure (NF) at low power by boosting the effective transconductance, while enhancing the linearity via suppressing the second-order harmonic distortion. Typically, the created loop gain of the CCC can raise the third-order intermodulation (IM3) distortion, penalizing the input-referred third-order intercept point (IIP3). Here, we propose a positive and a second capacitive feedback into the CCC CG transconductor, not only to suppress the IM3 distortion current but also adds in design flexibility to the input transistors. Furthermore, the positive feedback also improves the input impedance matching, conversion gain, and NF through a flexible design criterion. Prototyped in a 0.13- μm process, the proposed mixer operating at 900 MHz dissipates 4 mW at 1 V. The measured double sideband (DSB) NF is 8.5 dB, the conversion gain ( GC ) is 18.4 dB and the IIP3 is +12.5 dBm. © 1993-2012 IEEE.